THE ROLE OF ENTREPRENEURSHIP IN PROMOTING SUSTAINABLE DEVELOPMENT: SELECTED EXPERIENCES WITH SPECIAL REFERENCE TO IRAQ FOR THE PERIOD 2004-2020 (World Economics and Finance Bulletin, 2025)
Entrepreneurship is one of the most important contemporary topics due to its interconnected relationship with economic growth and sustainable development, especially in the projects of the organization, economic unity, and the adoption of small and medium enterprises. All international experiences confirm the growing positive impact of this field, especially in the local economic environments of most countries. These countries have mobilized their policies for an integrated system of entrepreneurship projects to contribute effectively within the general macroeconomic system of countries, by employing their potential to achieve tangible and effective tools, including reducing production costs, maximizing value-added returns, and preparing youth cadres and skilled workers to solve the country's problems of poverty, unemployment, and economic stagnation, and to stimulate economic production activity and the local market. The Iraqi economy needs entrepreneurship projects with the aim of formulating a comprehensive evaluation vision of the status of entrepreneurial projects and the extent of their impact on the structure of the Iraqi economy and achieving sustainable development.